2013
DOI: 10.1017/s1041610213001968
|View full text |Cite
|
Sign up to set email alerts
|

International Psychogeriatricsand the International Psychogeriatric Association: a successful marriage turns silver

Abstract: It is this time again to celebrate another milestone whichInternational Psychogeriatricshas reached. In 2014 the theme is silver, since it is a quarter of a century since the International Psychogeriatric Association (IPA), founded in 1982, andInternational Psychogeriatricsjoined forces in the quest to improve the mental health of older people around the globe. Our journal has matured since coming to life in 1989, growing up under the watchful eyes of a series of dedicated editors to come of age in 2009 (Ames,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
(3 reference statements)
0
9
0
Order By: Relevance
“…Nevertheless, it might be debatable whether commonly used screening tools are sensitive enough to detect small subtle changes, either deterioration or amelioration, in a patient's state [45] within a shorter period. As dementia research has progressed, the findings have demonstrated that the disease does not just affect cognition, but also other functions, such as motor [46], vision [47], and speech [38], possibly even from the early stages.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it might be debatable whether commonly used screening tools are sensitive enough to detect small subtle changes, either deterioration or amelioration, in a patient's state [45] within a shorter period. As dementia research has progressed, the findings have demonstrated that the disease does not just affect cognition, but also other functions, such as motor [46], vision [47], and speech [38], possibly even from the early stages.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge deficit about dementia was one of the most important factors that affected the ability of community health professionals to identify and diagnose people with dementia [ 13 , 14 ]. Inappropriate and delayed treatment of dementia, and misinterpretation of behavioural and psychological symptoms of dementia (BPSD) were reported and attributed to lack of dementia knowledge [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that more than nine million people suffer from dementia in China [ 16 ], which has immense financial implications for patients, caregivers, and society. However, China remains ill-prepared for the management of this disease with inadequate health care services for dementia [ 17 - 19 ]. In a population-based door-to-door caregiver survey, only 26.9% of patients with dementia in China report having received a diagnosis [ 20 ].…”
mentioning
confidence: 99%